Metabolomic and Transcriptomic Profiling Uncover the Underlying Mechanism of Color Differentiation in Scutellaria baicalensis Georgi. Flowers - Wang, Defu; Wang, Jiangran; Wang, Yufen; Yao, Dongzuo; Niu, Yanbing (Frontiers in Plant Science, 2022)
Scutellaria baicalensis Georgi. (Chinese skullcap or Huang-qin) is an extremely crucial medicinal plant in the Labiate family, and the color of its flowers naturally appears purple. However, during the long-term cultivation of S. baicalensis, very few plants of S. baicalensis also present white and purple-red flower colors under the same ecological conditions. However, the complex metabolic and transcriptional networks underlying color formation in white, purple-red, and purple flowers of S. baicalensis remain largely unclarified. To gain an insight into this issue, we conducted transcriptome and metabolomic profiling to elucidate the anthocyanin synthesis metabolic pathway in the flowers of S. baicalensis, and to identify the differentially expressed candidate genes potentially involved in the biosynthesis of anthocyanins. The results showed that 15 anthocyanins were identified, among which cyanidin 3-rutinoside and delphin chloride were the primary anthocyanins, and accumulation was significantly related to the flower color changes of S. baicalensis. Furthermore, the down-regulation of SbDFR (Sb02g31040) reduced the anthocyanin levels in the flowers of S. baicalensis. The differential expression of the Sb3GT (Sb07g04780 and Sb01g72290) gene in purple and purple-red flowers affected anthocyanin accumulation, suggesting that anthocyanin levels were closely associated with the expression of SbDFR and Sb3GT, which play important roles in regulating the anthocyanin biosynthesis process of S. baicalensis flowers. Transcriptomic analysis revealed that transcription factors WRKY, bHLH and NAC were also highly correlated with anthocyanin accumulation, especially for NAC35, which positively regulated SbDFR (Sb02g31040) gene expression and modulated anthocyanin biosynthesis in flower color variation of S. baicalensis. Overall, this study presents the first experimental evidence for the metabolomic and transcriptomic profiles of S. baicalensis in response to flower coloration, which provides a foundation for dynamic metabolic engineering and plant breeding, and to understand floral evolution in S. baicalensis plants.